Phenological observations, oil characteristics and equilibrium isotherm of Myroxylon peruiferum seeds (Fabaceae) - Aguilar-Sandí, Diego (2022)
Introduction. Phenological information on Myroxylon peruiferum in Costa Rica is scarce. In addition, the characteristics of the oil and the equilibrium isotherm are unknown. The knowledge generated in this field will allow proper seed management and generate oil prospecting options. Objectives. (i) To document a flowering and fruiting event of a single M. peruiferum tree. (ii) To determine the characteristics of the fruit and seed oil. (iii) To generate a water absorption/de-absorption isotherm. Materials and methods. From March to May 2021, the flowering and fruiting of M. peruiferum tree was documented in Montes de Oca, San Jose, Costa Rica. Mature fruits were collected between June and July. The oil content of fruits and seeds was characterized separately. A water absorption/de-absorption isotherm was elaborated, with which the fit of the Cromarty equation was tested. Results. The flowering, fruiting, and dispersal period lasted five months. These phenophases occurred simultaneously. Oleic acid was the main fatty acid. There was a significant correlation between the percentages of fatty acid in the fruit and seed oil, and between the contents of saturated, monounsaturated, and polyunsaturated fatty acids. The oil is yellow, moderately intense, and luminous. As relative humidity increased, seed moisture content also increased. The linear relationship between the actual values and those obtained using the Cromarty equation was R2= 0.93. Conclusion. Mature fruit can be harvested between March and August, and be used for germination, propagation and oil prospecting studies. Once the relationship between relative humidity and seed moisture content is established, studies on seed storage and viability loss can be developed.